Does The State Finance Cause the Green Finance Turbulence in Indonesia - Edwin Basmar; Zudi Setiawan; Hasan Hasan; Muhamad Takhim (Spektrum, 2026)
This study aims to propose priority solution to improve of green finance for create a balance used the financial state through intermediairy fungtion of banking sector as a form of economic growth circulation activities. On the other hand, the State financial are a determining system to improving green finance in achieving finance stability and economic growth in Indonesia. This study uses the Ed Wave Index development model based on Bank Indonesia financial report data, from the  balance theory, we rebuild new model with import of macroeconomic presssures as the finance circulation to analysis of green finance reaction for finance stability and economic growth in Indonesia. This study found that state financial have not been able to improve green finance in Indonesia, with conditions negative financial effectiveness, including periods 2, 4 and 5, on the other hand periods 1 and 3 where the opposite applies in Indonesian financial circulation. This study makes an important contribution to Bank Indonesia and the banking sector through the use of state finances to make green finance performance more effective, especially in achieving financial stability and economic growth in Indonesia.